The presence of left-wing militant women within projects of poder popular during the Popular Unity years in Concepción and Santiago de Chile, 1970–3. (1st June 2021) - Inostroza Retamal, Gina
Abstract : This article analyses, from a gender perspective, the socio-political experiences of eight former left-wing militant women in processes linked to so-called poder popular (popular power). It does so with a focus on poblaciones (shantytowns) and trade unions in Concepción and Santiago between 1970 and 1973. Methodologically, it takes a qualitative approach, contrasting oral history interviews with primary sources. The process of political socialisation in childhood and adolescence influenced women when it came to joining political parties on both the 'traditional left' and the 'revolutionary left'. At the start of the 1970s, these militants participated in grassroots organisations, such as juntas de abastecimiento y precios (supply and price control boards, JAPs), shantytowns, centros de madre (mothers' centres) and unions, among others. This meant that their practices as party militants had a high degree of continuity with lived social experiences from their youth. The main difference was that as party militants they moved through more politicised spaces and gained access to political training and, in some cases, took on leadership roles within social organisations. Indeed, one woman became a communal – and later, parliamentary – representative. The skills acquired and their experiences during the Popular Unity (UP) period shaped their life trajectories, and consequently, these women have promoted an intergenerational transfer of socio-political practices in new, contemporary Chilean, scenarios.